PELATIHAN PENASKAHAN SURAT DINAS DI KELURAHAN JAHAB, KECAMATAN TENGGARONG, KABUPATEN KUTAI KARTANEGARA : Business Correspondence Training in Jahab Village, Tenggarong Subdistrict, Kutai Kartanegara District - Arifin, M. Bahri; Wahyuni, Ian; Tawakal, Alamsyah; Vivian, Yofi Irvan; Yudista, Rensiana (Program Studi Sastra Indonesia Universitas Mulawarman, 2022)
Letter activity - correspondence is an indirect communication process carried out by an institution or agency. Effective delivery of information can be achieved by armed with basic knowledge of correspondence writing, linguistic rules, and letter forms, so that the intent and purpose of the letter is well received by the recipient of the letter. In addition, digital knowledge of archiving is also needed for data storage. The method used in the official letter scripting training, namely the direct method with mentoring, question and answer, and instructional techniques in writing official correspondence. The training participants consisted of thirteen people consisting of the village head, secretary of the village head, section head, and staff of Jahab Village, Tenggarong Subdistrict, Kutai Kartanegara District. The results of this activity are in the form of improving the performance capability of the Jahab Village apparatus in the distribution of public administration correspondence in terms of mastery of correspondence science, the requirements for official letters by referring to the national rules for official manuscripts, the language of official letters must be effective, reasonable, logical, efficient, careful, polite, and interesting. It is also necessary to know that note that the letter format or format of the letter varies, including: full straight shape, straight shape, half straight shape, notched shape, old Indonesian form, new Indonesian form, hanging shape. Digital archiving training is also needed in addition to being economical, safe, and practical as well as increasing the capacity of village human resources to be able to keep up with the globalsasid flow in the digital industry era.